E-Library Menggunakan Metode K-Means Mengkategorikan Buku Berdasarkan Judul Buku dengan Berbasis Website - Izuddin Alqosam (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Technology and information in the digital era is developing very rapidly, especially in the field of information systems. Along with advances in technology we can alleviate an existing problem. Given the rapid development of information systems in recent years, it can encourage human activity to seek information. One of the technological developments marked by the existence of the internet is providing services. The forms of services provided by the internet are useful and beneficial for human life, from data access, advertising, communication, actual information, and one of them is a digital library or can be called E-Library. A library is a collection or collection of all kinds of books, archives and papers. A library management system that is still manual requires the role of technology. So we need E-library technology to implement a library management system to facilitate library management. researchers are encouraged to study the E-library by using the K-Means Clustering method to solve E-Library problems.